Aligning Student Needs with English Curriculum in Indonesian Junior High School - Fadhliyah Rahmah Muin; Andi Musafir Rusyaidi (Universitas Islam Negeri Palopo, 2025)
The alignment between students’ learning needs and the English curriculum in an Indonesian junior high school context. This response concerns the degree to which students’ target needs and learning needs match with the teacher’s views, she said, followed by debate on how this aligns to actual practices of English in classroom settings. This study uses a descriptive qualitative design involving an English teacher and a group of junior high school students. Three instruments were used for data collection: a student questionnaire on necessities, lacks, wants and activities; a semi-structured teacher interview and classroom observation. The data were systematically categorized, interpreted to identify patterns and mismatches. The results reveal that students’ competence in English is still at a low level, especially in vocabulary mastery and speaking confidence, whilst the majority of students have strong proclivities to interactive, communicative and technology-supported learning activities. The study also finds a partial misalignment between the goals of lesson plans overall and actual classroom practices. This reminds us that relevant implementation of a curriculum should be based on the actual learning needs of students—it realistically allows: enhanced vocabulary support, use of language in practice and engaging methods being implemented – leading to more responsive and student-focused English teaching practices as a whole.